SMART TOURISM AND ITS IMPACT ON HORECA - Kryvokhyzha, Yevhen; Hryhorchak Ігор; Terletska, Khrystyna (Social Development: Economic and Legal Issues, 2026)
Modernization of business models in the tourism sector requires updating communication strategies and information support systems for companies’ activities. Therefore, the integral components of upgrading approaches to doing business in the tourism and hospitality sector are the stimulation of investments and technological innovations, the implementation of modern digital solutions, comprehensive automation of service, and the expansion of marketing strategies. The study is aimed at an extended analysis of the phenomenon of smart tourism and aspects of its impact on the hotel, restaurant and catering (HoReCa) sector. The article substantiates the importance of introducing modern digital innovations in the tourism sector to increase the efficiency of activities, expand the client audience and create a unique experience to maximize the satisfaction of its requests, optimize internal management, and achieve sustainable development of the industry. The key aspects of the impact of smart tourism on the HoReCa industry are considered to be deep personalization of service, automation of routine processes, systemic digitalization, and transition to a sustainable development model. This approach allows optimizing operating costs and increasing customer loyalty. It is obvious that achieving sustainability of smart destinations in the field of tourism and hospitality requires coordination of the system of production and consumption of tourist services using smart technologies. The key vectors of functioning of such a system are considered to be ensuring social responsibility, effective information management, digital communication, and convergence of tourist experience and technologies and global tourism markets. The study proves that the gradual digitalization of the tourism sector using smart technologies allows for effective management of tourist flows, integration of travel planning tools and destination visits, which allows the hospitality sector to be involved for infrastructure support within target platforms in the context of popular destinations to ensure long-term stability.